Efficacy of different intensities of percutaneous electrolysis for musculoskeletal pain: A systematic review and meta-analysis - Sánchez-González, Juan Luis; Navarro-López, Víctor; Cañada-Sánchez, Pablo; Juárez-Vela, Raúl; Viñaspre-Hernández, Regina Ruiz de; Varela-Rodríguez, Sergio (Frontiers in Medicine, 2023)
Objective A meta-analysis of randomized controlled trials (RCTs) was conducted to determine the effect of ultrasound-guided percutaneous electrolysis (PE) alone or as an adjunct to other interventions on pain intensity generated by musculoskeletal disorders, depending on the intensity of the technique. Data sources PUBMED, EMBASE, Cochrane Library, Web of Science, SCOPUS, Health Medical Collection, and CINALH from inception to September 2022 were searched to identify documents. Study selection Publications investigating the effect of ultrasound-guided PE in musculoskeletal pain. Data extraction Data were extracted into predesigned data extraction and tables. Risk of bias was evaluated with the Cochrane Risk of Bias Tool (Rob 2.0). Thirteen articles met inclusion criteria. Data analysis Random-effects meta-analysis models were used to quantify the difference in pain between the PE and control groups. Data synthesis A significant reduction in pain was found in favor of low- (−1.89; 95% CI: −2.69; −1.10; p < 0.001) and high-intensity PE (−0.74; 95% CI: −1.36; −0.11; p: 0.02) compared to control group. Low-intensity PE showed significant reduction in pain in the short (−1.73; 95% CI: −3.13; −0.34; p < 0.02) and long term (−2.10; 95% CI: −2.93; −1.28; p = 0.005), with large effect sizes compared to control group. High-intensity PE only showed significant lower pain than control group in the long term (−0.92; 95% CI: −1.78; −0.07; p < 0.03), with a small effect size, but not in the short term. Conclusion We found small evidence suggesting that low-intensity PE could be more effective for musculoskeletal pain reduction than high-intensity PE. Nevertheless, scientific evidence on this subject is still scarce and studies comparing the two modalities are warranted. Systematic review registration www.crd.york.ac.uk/prospero, identifier CRD42022366935.